2022
DOI: 10.1039/d1fo03949k
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Alpinia officinarum Hance polysaccharide and its immune modulatory activity in mice

Abstract: This study aimed to verify the regulating effect of a novel water-soluble polysaccharide (AOHP) extracted from Alpinia officinarum Hance on mouse immunity and to characterize its structure feature. The cellulose...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Notably, the AOPs were rich in glucose, especially AOP30 (89.88%). This result is consistent with that of a previous study [30], whereas the level of galactose in AOP50 and AOP70 was eight times higher than that found in AOP30.…”
Section: Molecular Weights Monosaccharide Compositions and Zeta Poten...supporting
confidence: 93%
“…Notably, the AOPs were rich in glucose, especially AOP30 (89.88%). This result is consistent with that of a previous study [30], whereas the level of galactose in AOP50 and AOP70 was eight times higher than that found in AOP30.…”
Section: Molecular Weights Monosaccharide Compositions and Zeta Poten...supporting
confidence: 93%
“…Compared with SCCP, the prominent absorption peaks did not change remarkably in the polysaccharide-iron (III) complexes prepared at four different temperatures. The absorption peak near 3340 cm −1 was mainly caused by the −OH stretching vibration, and the absorption peak near 1650 cm −1 was mainly due to the C=O asymmetric vibration of −COOH in the polysaccharide [ 21 ]. It also shows that the absorption peak around 1400 cm −1 reflects the symmetric vibration of C−O in −COOH.…”
Section: Resultsmentioning
confidence: 99%
“…The AHP-3a monosaccharide composition was determined as per the method suggested by Ni et al [21]. Briefly, AHP-3a (5 mg) was hydrolyzed using 3 mol/L TFA at 120 • C for 3 h. The hydrolyzed product was dried under a nitrogen-filled atmosphere, washed with methanol to remove residual TFA, and dissolved in water.…”
Section: Chemical and Monosaccharide Composition Analysesmentioning
confidence: 99%
“…On investigating the biological activity of the A. officinarum crude polysaccharide, Hailiwu et al found that the polysaccharide could successfully suppress the growth of the murine forestomach carcinoma cell line (MFC) stomach cancer xenograft in mice [20]. Following a comprehensive structural examination, Ni et al reported that the neutral polysaccharide of A. officinarum possesses immunomodulatory properties [21]. Most of these past reports are focused on A. officinarum crude and neutral polysaccharides, and there have been no studies on the structural properties and biological activities of A. officinarum acidic polysaccharides.…”
Section: Introductionmentioning
confidence: 99%